Factors Associated with Risky Sexual Behavior in Adolescents in Indonesia Rural Areas - Setiawati Nina; Susmarini Dian; Kartikasari Aprilia; Anggraeni Mekar Dwi; Latifah Lutfatul; Rahmawati Eni (E3S Web of Conferences)
Adolescence is a transitional period from childhood to adulthood, marked by rapid physical, psychological, and social changes that can impact the development of sexual behaviours, including the potential for engaging in risky sexual behaviour. This study aimed to identify factors that influence risky sexual behaviour in adolescents in Indonesia's Rural Areas. This study is a quantitative research with a cross-sectional design. The sample of this study was active students in Banyumas Regency, one of Indonesia’s rural areas in 2022. A probability sampling technique with proportional stratified random sampling was used and obtained 452 respondents. The data was collected using questionnaire sheets. Data were analyzed using the Chi-Square and multiple logistic regression tests. This study shows that dating experience, dating status, age, religiosity and access to technology are the most influential factors for risky sexual behaviour in adolescents in rural areas, with dating experience having the greatest influence as indicated by an OR value of 6.67. Although religiosity plays a role, it is insufficient to protect adolescents from risk. Comprehensive sexual health education and consistent monitoring of technology usage are urgently needed to reduce risky sexual behaviours among adolescents in rural areas.